2011
DOI: 10.2214/ajr.11.6424
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Biliary Metallic Stent Placement in Patients With Unilobar Portal Vein Occlusion Caused by Advanced Hilar Malignancy: Outcome of Unilateral Versus Bilateral Stenting

Abstract: Unilateral biliary metallic stent placement in the lobe with a patent portal vein seems to be a safe and effective palliative treatment of patients with contralateral portal vein occlusion caused by advanced hilar malignancy, obviating bilateral stent placement in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 21 publications
(28 reference statements)
0
31
3
1
Order By: Relevance
“…However, Iwano et al [6] failed to find any significant benefits of bilateral drainage on stent patency time and survival. However, hepatic lobar atrophy frequently co-occurs with hilar cholangiocarcinoma and has been reported to occur in 20-30% of patients with this diagnosis [18]. However, hepatic lobar atrophy frequently co-occurs with hilar cholangiocarcinoma and has been reported to occur in 20-30% of patients with this diagnosis [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, Iwano et al [6] failed to find any significant benefits of bilateral drainage on stent patency time and survival. However, hepatic lobar atrophy frequently co-occurs with hilar cholangiocarcinoma and has been reported to occur in 20-30% of patients with this diagnosis [18]. However, hepatic lobar atrophy frequently co-occurs with hilar cholangiocarcinoma and has been reported to occur in 20-30% of patients with this diagnosis [18].…”
Section: Discussionmentioning
confidence: 99%
“…When the portal Fig. 6 Kaplan-Meier curve of the stent patency rate vein of one liver lobe is obstructed, portal vein obstruction interrupts the cycle of enterohepatic circulation in the obstructed lobe (14,15). Previous investigators reported successful treatment of bile leakage by selective portal vein embolization, which induces cessation of bile production (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…30,33 SEMS placement is generally performed within 1 to 2 weeks after PTBD and relieves jaundice or cholangitis. 8,13,22 Access Route Bilateral (multiple) percutaneous routes Bilateral (multiple) percutaneous routes allow for easy handling and negotiation of a guidewire into the common bile duct (CBD) through the stricture caused by the tumor. SEMS placement via bilateral access is also technically simple.…”
Section: Percutaneous Transhepatic Biliary Drainagementioning
confidence: 99%
“…It is generally performed using the stent-in-stent technique (T configuration or Y configuration) or the side-by-side technique. 8,12,13,22,[25][26][27][28] In addition, the crisscross technique has been reported as being a useful method for trisegmental drainage. 10 The side-to-end technique is also useful for multiple SEMS placement.…”
Section: Metallic Stent Placement Techniquementioning
confidence: 99%
See 1 more Smart Citation